2013
DOI: 10.14429/djlit.33.2.4201
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Weblink Analysis among Top Indian, Asian and World universities

Abstract: The article investigates the relationship among top ten world universities (TTWU), top ten Asian universities (TTAU) and top ten Indian universities (TTIU) based on the exploratory study of weblink analysis. Inlinks and outlinks analysis try to explore the relationship among these universities. The findings suggest that although TTIU are generating 3.71 % outlinks to TTWU but receives only 0.67 % inlinks from them. On the other hand, inlinks and outlinks to TTAU are far less than TTWU. An interesting result re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Jalal 10 found that the relationship through link analysis that inlinks/outlinks to top ten Asian Universities are far less than top ten world universities. The percentage of inlinks and selflinks for top ten Indian and Asian universities were less than top ten world universities under study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jalal 10 found that the relationship through link analysis that inlinks/outlinks to top ten Asian Universities are far less than top ten world universities. The percentage of inlinks and selflinks for top ten Indian and Asian universities were less than top ten world universities under study.…”
Section: Literature Reviewmentioning
confidence: 99%